2019
DOI: 10.1158/1535-7163.mct-18-0832
|View full text |Cite
|
Sign up to set email alerts
|

Combining DNA Vaccine and AIM2 in H1 Nanoparticles Exert Anti-Renal Carcinoma Effects via Enhancing Tumor-Specific Multi-functional CD8+ T-cell Responses

Abstract: Renal carcinoma presents a rapid progression in patients with high metastasis with no effective therapeutic strategy. In this study, we designed a folate-grafted PEI600-CyD (H1) nanoparticle-mediated DNA vaccine containing an adjuvant of absent in melanoma 2 (AIM2) and a tumor-specific antigen of carbonic anhydrase IX (CAIX) for renal carcinoma therapy. Mice bearing subcutaneous human CAIX (hCAIX)-Renca tumor were intramuscularly immunized with H1-pAIM2/pCAIX, H1-pCAIX, H1-pAIM2, or Mock vaccine, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…T cell reactivity against AIM2 has been found in patients with melanoma, suggesting that AIM2‐derived peptides are an ideal candidate for immunomonitoring 95 . Indeed, as a sensor of DNA, AIM2 induces an antigen‐specific antibody response and is used as an adjuvant to enhance therapeutic efficacy through CD8 + T cell adaptive immunity 39–42 . For example, AIM2 promotes the multifunctional CD8 + T cell activation elicited by the viral capsid protein 1 vaccine, 39 which favors long‐lasting protection against Coxsackievirus B 3 ‐induced myocarditis 40 .…”
Section: Role Of Aim2 In Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…T cell reactivity against AIM2 has been found in patients with melanoma, suggesting that AIM2‐derived peptides are an ideal candidate for immunomonitoring 95 . Indeed, as a sensor of DNA, AIM2 induces an antigen‐specific antibody response and is used as an adjuvant to enhance therapeutic efficacy through CD8 + T cell adaptive immunity 39–42 . For example, AIM2 promotes the multifunctional CD8 + T cell activation elicited by the viral capsid protein 1 vaccine, 39 which favors long‐lasting protection against Coxsackievirus B 3 ‐induced myocarditis 40 .…”
Section: Role Of Aim2 In Immune Cellsmentioning
confidence: 99%
“…For example, AIM2 promotes the multifunctional CD8 + T cell activation elicited by the viral capsid protein 1 vaccine, 39 which favors long‐lasting protection against Coxsackievirus B 3 ‐induced myocarditis 40 . Similarly, AIM2‐adjuvant vaccines exhibit antitumor therapeutic efficacy by heightening tumor‐specific CD8 + T cell immunity 41 . The involvement of AIM2 in vaccine‐induced immune responses requires type I IFN signaling via cGAS‐independent STING‐IRF7 signaling 96 .…”
Section: Role Of Aim2 In Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vault NPs Large cytoplasmic ribonucleoprotein particles NLRP3 [32] Chitosan Biodegradable cationic polymer obtained from chitin NLRP3 [10,[33][34][35][36] Silica particles Biocompatible particles NLRP3 [37,38] Gold NPs Gold nanoparticles NLRP3 [39] Flagellin Used as recombinant protein, or encoded in virus replicon or DNA plasmid NLRC4 [40][41][42][43][44] DNA vaccines DNA plasmids or Aim2 encoded in vector as immunopotentiator AIM2 [45][46][47] CTB Cholera toxin B from Vibrio cholerae, added to an Ag, or as a DNA vaccine NLRP3, Pyrin [48][49][50] oxPAPC Oxidized 1-palmitoyl-2-arachidonoyl-snglycero-3-phosphorylcholine (generated during tissue damage)…”
Section: Description Targeted Inflammasome Referencesmentioning
confidence: 99%
“…Interestingly, IFN-α/β were reduced in Aim2-deficient mice after DNA vaccination, which might indicate that DNA vaccines induce IFN-α/β signalling, thereby promoting dispensability of IL-1/IL-18 signalling [46]. Recently, two studies demonstrated that DNA vaccines encoding the Aim2 gene itself might be a promising approach to enhance immunogenicity [45,47].…”
Section: Aim2 Inflammasomementioning
confidence: 99%